2016
DOI: 10.1021/jacs.6b09759
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective and Stereoselective trans-Hydroboration of 1,3-Enynes Catalyzed by 1,4-Azaborine-Based Phosphine–Pd Complex

Abstract: A concise synthesis of monobenzofused 1,4-azaborine phosphine ligands (Senphos) is described. These Senphos ligands uniquely support Pd-catalyzed trans-selective hydroboration of terminal and internal 1,3-enynes to furnish corresponding dienylboronates in high efficiency and diastereoselectivity. X-ray structural analysis of the Senphos–Pd(0) complex reveals a κ2-P-η2-BC coordination mode, and this isolated complex has been shown to serve as a competent catalyst for the trans-hydroboration reaction. This work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(57 citation statements)
references
References 46 publications
2
55
0
Order By: Relevance
“…[76] Later,L iu et al disclosed the Pd-catalyzed trans hydroboration of terminala nd internal 1,3-enynes with high selectivity and stereoselectivity assisted by 1,4-azaborine-based phosphine ligands. [77] In the case of functionalized alkynes, such as alkynoate esters or amides, [78] propargylic alcohols and ethers, [79] thioacetylenes, [80] or ynamides, [81] differentc opper catalysts (or metalfree phosphine catalysis in the prior case) have been employed to induce a or b selectivity,with both regioisomers being available in all cases.T he hydroboration of allenesh as also been exploited for the synthesis of trisubstituted alkenes, with the catalysta sw ell as the substituents influencing the regioselectivity of the process to the internal or distal double bond. [64b, 82] Another strategy for the synthesis of tri-and tetrasubstituted alkenyl boronates is the carboboration of alkynes or allenes to generate new CÀBa nd CÀCb onds (Scheme 20).…”
Section: Synthesis Of Tri-and Tetrasubstituted Alkenyl Boronatesmentioning
confidence: 99%
“…[76] Later,L iu et al disclosed the Pd-catalyzed trans hydroboration of terminala nd internal 1,3-enynes with high selectivity and stereoselectivity assisted by 1,4-azaborine-based phosphine ligands. [77] In the case of functionalized alkynes, such as alkynoate esters or amides, [78] propargylic alcohols and ethers, [79] thioacetylenes, [80] or ynamides, [81] differentc opper catalysts (or metalfree phosphine catalysis in the prior case) have been employed to induce a or b selectivity,with both regioisomers being available in all cases.T he hydroboration of allenesh as also been exploited for the synthesis of trisubstituted alkenes, with the catalysta sw ell as the substituents influencing the regioselectivity of the process to the internal or distal double bond. [64b, 82] Another strategy for the synthesis of tri-and tetrasubstituted alkenyl boronates is the carboboration of alkynes or allenes to generate new CÀBa nd CÀCb onds (Scheme 20).…”
Section: Synthesis Of Tri-and Tetrasubstituted Alkenyl Boronatesmentioning
confidence: 99%
“…The first strategy has been recognized as useful in modulating the singlet–triplet energy gaps and paratropicity of 4 n π‐electron systems . BN/CC isosterism has also been widely exploited to tune various molecular properties and hybrid BN/CC compounds have been employed in materials science, medicinal chemistry, and synthetic chemistry . A number of theoretical and experimental studies have shown that various molecular properties, such as singlet–triplet energy gaps, spin state, aromaticity, and antiaromaticity, can be controlled by introducing substituents into the basic molecular structure…”
Section: Introductionmentioning
confidence: 99%
“…[3a, 6b, 7, 8] BN/CC isosterism has also been widely exploited to tune various molecular properties [9] and hybrid BN/CC compounds have been employed in materials science, [10] medicinalc hemistry, [11] and synthetic chemistry. [12] An umber of theoreticala nd experimental studies have shown that variousm olecular properties, such as singlet-triplet energy gaps, spin state, aromaticity,a nd antiaromaticity,c an be controlled by introducing substituents into the basic molecular structure. [13] The results of the work presented herein could guide experimental chemists in which way to modify the basic structure of [a,f]DBP to produce compounds with desirable properties.…”
Section: Introductionmentioning
confidence: 99%
“…This transformation requires a large excess of the alkyne and the use of an organometallic compound under harsh conditions compromises the functional group tolerance (Scheme c). The trans ‐selective hydroboration of enynes represents an alternative to the use of organometallic reagents (Scheme d) . However, its reductive nature precludes the challenging formation of highly substituted 1,3‐dienes .…”
Section: Methodsmentioning
confidence: 99%